Viatorr Stent Migration and Retrieval during Transjugular Intrahepatic Portosystemic Shunt Revision - Kim, Stephanie H.; Samuel, Michael; Makramalla, Abouelmagd (Seminars in Interventional Radiology, 2023)
Transjugular intrahepatic portosystemic shunt (TIPS) is an important interventional option for the treatment of complications related to cirrhosis and portal hypertension. Emergent TIPS placement can be a life-saving measure in patients with uncontrolled variceal hemorrhage. After TIPS placement, patients may benefit from additional interventions for clinical optimization including stent dilation, stent extension, and embolization of varices. Here, we describe a case of emergent TIPS placement and revision which resulted in TIPS stent migration requiring stent removal and replacement. We discuss our technique and review previously reported methods for the management of migrated TIPS stents.
Keywords: interventional radiology; transjugular intrahepatic portosystemic shunt; foreign body retrieval; Viatorr